Applied Pragmatics Use in Post-Pandemic of English Language Learning - Farid Noor Romadlon; Abdulhamid Badru (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
The importance of meaning in communication is significant, and they can be classified into two categories: Verbal and non-verbal. Various circumstances, the dynamic between speakers, and social elements all have a role. The four language abilities of language acquisition reading, writing, listening, and speaking do not occur in isolation in communicative texts or activities, hence pragmatics in English language learning is crucial. For the language student, developing good pragmatic competence should be taken into account. The application of applied pragmatics in post-pandemic English language learning is discussed in this essay. English-speaking users, both native and non-native, should speak clear, understandable and educated English, as this facilitates communication and reduces the risk of misunderstandings in social situations. In international communication, English has been crucial. In order to successfully achieve their communicative objectives in cross-cultural communication, language users might benefit from pragmatic competence. Therefore, pragmatic aspects play a significant role in communication between speakers as they can prevent misunderstandings and errors during conversation. As a result, teachers should include pragmatic competency in English language classrooms through a variety of tasks and exercises.